1989
DOI: 10.1002/ps.2780250404
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated degradation of thiocarbamate herbicides in Israeli soils following repeated use of vernolate

Abstract: Accelerated degradation of vernolate, EPTC and butylate but not of cycloate was detected in soils from three locations in Israel which were treated annually with vernolate. Repeated application of EPTC to soils with and without a history of vernolate application, under laboratory conditions, resulted in a progressive increase in its rate of dissipation with each application. Accelerated degradation of EPTC was also rapidly induced by mixing small amounts (5%) of soil with a history of vernolate treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
9
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
6
9
0
Order By: Relevance
“…The half-life times of free EPTC incorporated into sandy soil were 15.5 and 17 days as determined by root and shoot lengths of oat seedlings, respectively (Figures 9 and 10). These data are in agreement with those reported by Tal et al (1989) for EPTC behavior in sandy soils. Using either Mont-EPTC or SepEPTC, with or without MG, did not change the dissipation pattern of the herbicide but resulted in a half-life time 1 week longer than that of free EPTC.…”
Section: T I M E Of Incubation (Weeks)supporting
confidence: 95%
“…The half-life times of free EPTC incorporated into sandy soil were 15.5 and 17 days as determined by root and shoot lengths of oat seedlings, respectively (Figures 9 and 10). These data are in agreement with those reported by Tal et al (1989) for EPTC behavior in sandy soils. Using either Mont-EPTC or SepEPTC, with or without MG, did not change the dissipation pattern of the herbicide but resulted in a half-life time 1 week longer than that of free EPTC.…”
Section: T I M E Of Incubation (Weeks)supporting
confidence: 95%
“…These compounds are considered hazardous because they potently inhibit acetylcholine esterase (9) and the N-nitrosocarbamates formed are potent mutagens (8). On the other hand, these pesticides generally do not persist in soil for a long time, and the persistence of these compounds in agricultural soil is due to repeated applications (10,38). From these perspectives, an understanding of the degradation mechanism is needed to control the persistence of these pesticides in soil.…”
mentioning
confidence: 99%
“…Many authors have suggested that microbial degradation plays an important role in the reduction of the accumulation of the pesticide residues. However, the microbial degradation of the pesticides may be so rapid as to reduce the efficacy against the target pest (9,21). Therefore, much attention has focused on the microbial degradation of carbamate pesticides.…”
mentioning
confidence: 99%